Defective construction work and the project team - Barrett, Kevin, LLB, FCIArb (Oxford ; Ames, Iowa : Wiley-Blackwell, 2008)
Defective construction work, whether the result of inadequate design, faulty workmanship or poor materials or some combination of these failings is a frequent cause of legal disputes. Someone is usually to blame, either the builder or one or more of the professional consultants, or even the entire project team. It is important therefore that the project team should possess a good working knowledge of their responsibilities and liabilities. Written by a solicitor with over twenty years of experience of building disputes, this book examines the responsibilities and liabilities of the project team when defects occur. It sets out the background role of the common law and statute and includes detailed discussion of important case law affecting the construction process from inception through to completion, together with a consideration of the impact of letters of intent, no contract situations, and specific provisions of model conditions of contract.
Includes bibliographical references (page 196) and index.
Print version record.
John Wiley and Sons
Keywords: Great Britain; Construction contracts -- England; Liability for building accidents -- England; Premises liability -- England; z; LAW -- Military; Construction contracts; Liability for building accidents; Premises liability; England